2002
DOI: 10.1021/jo020568l
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Leinamycin by Thiols:  A Theoretical Study

Abstract: Reaction of thiols with the 1,2-dithiolan-3-one 1-oxide heterocycle found in leinamycin (1) results in the conversion of this antitumor antibiotic to a DNA-alkylating episulfonium ion (5). While the products formed in this reaction have been rationalized by a mechanism involving initial attack of thiol on the central sulfenyl sulfur (S2') of the 1,2-dithiolan-3-one 1-oxide ring, the carbonyl carbon (C3') and the sulfinyl sulfur (S1') of this heterocycle are also expected to be electrophilic. Therefore, it is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…Previous studies have shown that along with DNA alkylation, leinamycin produces reactive oxygen species (ROS) from the persulfide species generated in the reaction of thiols with leinamycin [6,8]. A recent study in our lab showed that leinamycin was able to generate oxidative stress in the MiaPaCa human pancreatic cancer cell line [22].…”
Section: Nac Reduces Leinamycin-induced Oxidative Stress In Mda-mb-23mentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have shown that along with DNA alkylation, leinamycin produces reactive oxygen species (ROS) from the persulfide species generated in the reaction of thiols with leinamycin [6,8]. A recent study in our lab showed that leinamycin was able to generate oxidative stress in the MiaPaCa human pancreatic cancer cell line [22].…”
Section: Nac Reduces Leinamycin-induced Oxidative Stress In Mda-mb-23mentioning
confidence: 98%
“…Previous studies suggest that the 1, 2-dithiolan-3-one 1-oxide in leinamycin is the primary target of thiol attack as described in Figure 1 [6][7][8]. This reaction leads to the conversion of this heterocyle to a 1, 2-oxathiolan-5-one which undergoes a novel rearrangement reaction to produce a DNA attacking episulfonium ion [6][7][8]. This episulfonium ion associates noncovalently with the double stranded DNA and alkylates the N7 position of the guanine residue very efficiently [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations